Laparoscopic anatomic resection of segment 7 of the liver using the intrahepatic Glissonean approach from the dorsal side (with video). (29th October 2019) - Ome, Yusuke; Seyama, Yasuji; Doi, Manami
Abstract : Laparoscopic anatomic resection of S7 is challenging. Ome and colleagues described an intrahepatic approach to the S7 Glissonean pedicles from the dorsal side without dissection around the hepatic hilum, allowing safe exposure of the right hepatic vein in the same view. This approach is safe and offers advantages for later hepatectomy.